Metals concentration in freshwater fish from Doce River and the influences of the Samarco’s Dam collapse, Mariana, Brazil - Ferreira, Frederico Fernandes (2022)
The Rio Doce basin is located in southeastern Brazil, in the states of Minas Gerais (MG) and Espírito Santo (ES). The basin is characterized by intense economic activity, which, added to the high population density and historical processes of extractivism, makes it one of the Brazilian drainages most impacted by human activities. With the disposal of domestic sewage, agricultural and industrial inputs in the channel of the Doce River and its tributaries, violations of water quality parameters such as total phosphate and fecal coliforms are historically recorded for the basin. The collapse of the SAMARCO dam threw 62 tons of tailings into the Doce River channel. Covering fish microhabitats, foraging and breeding areas, aggravating the state of degradation of the basin and modifying the physical and chemical characteristics of the river bed sediment. The tailings avalanche turned over the river bottom, resuspending the sediment and bio making available metals that were previously trapped in lower river layers. The composition of the tailings is mainly silica and iron oxides, but studies indicate high levels of other elements such as Aluminum, Arsenic and Manganese. Thus, the tailings contributed directly and indirectly to the mobilization of metals for the aquatic biota. Bioaccumulation within fish and biomagnification of metals in the food chain can generate irreversible impacts on aquatic biota given its persistence in biota, not being decomposed, increasing its toxicity. Our results indicate mercury biomagnification and bioaccumulation of several elements such as arsenic and mercury, for several of the studied species, and the result varies in an interspecific way. Some species are more subject to bioaccumulation, among them those with piscivorous and benthic habits stand out. These groups should be a priority target for monitoring the concentrations of metals in the ichthyofauna with a focus on food security and maintenance of fish communities in the basin. Among the tributaries studied, the Gualaxo do Norte and Carmo rivers deserve special attention, mainly due to the high mercury values recorded for the region's ichthyofauna. The historic gold extraction process in the region and the leaching and contamination of aquatic biota makes these tributaries the main target for monitoring and bioremediation studies. Keywords: Fish. arsenic. Mercury. Bioaccumulation. Trophic level.